Initiation and growth kinetics of solidification cracking during welding of steel - Aucott, L; Huang, D; Dong, H; Wen, S; Marsden, J; Rack, A; Cocks, A (Nature Publishing Group, 2017)
Solidification cracking is a key phenomenon associated with defect formation during welding. To elucidate the failure mechanisms, solidification cracking during arc welding of steel are investigated in situ with high-speed, high-energy synchrotron X-ray radiography. Damage initiates at relatively low true strain of about 3.1% in the form of micro-cavities at the weld subsurface where peak volumetric strain and triaxiality are localised. The initial micro-cavities, with sizes from 10 × 10−6 m to 27 × 10−6 m, are mostly formed in isolation as revealed by synchrotron X-ray micro-tomography. The growth of micro-cavities is driven by increasing strain induced to the solidifying steel. Cavities grow through coalescence of micro-cavities to form micro-cracks first and then through the propagation of microcracks. Cracks propagate from the core of the weld towards the free surface along the solidifying grain boundaries at a speed of 2–3 × 10−3 m s−1.